Transesterification of Waste Cooking Oil using CaO Catalyst Derived from Madura Limestone for Biodiesel Production and Its Application in Diesel Engine - Abdul Hamid; Amin Jakfar; Sirly Bifadilatur Romaniyah; Ike Dayi Febriana; Mohammad Abdullah; Zeni Rahmawati; Didik Prasetyoko (Universitas Muhammadiyah Magelang, 2023)
In this study, we report biodiesel production from waste cooking oil using CaO catalyst derived from Madura limestone through a transesterification reaction. Many limestone quarries in Madura can be used as heterogeneous catalysts because they are cheap, easy to separate, and have high basicity. Conversion of limestone into CaO catalyst through calcination at 900Â°C for 3 hours. The CaO catalyst formed was characterized using X-Ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR), and Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX) instruments. Biodiesel formed through the transesterification reaction was analyzed using GC-MS. Furthermore, biodiesel blends from waste cooking oil and pure diesel were prepared in volume percentages (B-10, B-20, B-30, B-40, and B-100) for testing on diesel engine performance. The results of testing the highest torque and brake horsepower (BHP) were obtained on pure diesel fuel (S-100) at 2.49 Nm and 381.12 watts, respectively. The lowest fuel consumption at 1500 rpm is produced on the B-20 at 0.186 kg/h. Overall, the emission characteristics of carbon monoxide (CO), nitrogen oxides (NOx), and nitrogen monoxide (NO) with the lowest concentration resulted from biodiesel blends rather than pure diesel.